Isolation of an Unusual Mycobacterium Species from an AIDS Patient with Acute Lymphadenitis - Bajolet, Odile (American Society for Microbiology, 2000)
A nonchromogenic Mycobacterium species was isolated from an AIDS patient with acute lymphadenitis. On the basis of the results of conventional tests, the strain appeared to be an atypical nonphotochromogenic Mycobacterium kansasii strain. Sequencing of the 16S rRNA gene revealed a unique nucleic acid sequence, suggesting that the isolate represents an undescribed pathogenic species.